Actress of a certain age : my twenty year trail to overnight success - Hiller, Jeff (Simon & Schuster, 2025)
Jeff Hiller's memoir is a funny, honest account of his long, often unglamorous journey to success as an actor. After decades of temp jobs and small roles, he finally found his breakout on HBO's Somebody Somewhere at forty. Blending humor and heart, Hiller reflects on growing up gay and Lutheran in Texas, facing rejection, and holding on to dreams despite setbacks. It's a relatable story for anyone who's ever struggled to make a dream come true.